Search for time-reversal-symmetry violation in thallium fluoride using a jet source - Cho,D; Sangster,K; Hinds,EA (Physical Review A, 1991)
We have looked for a violation of time-reversal symmetry (T) in the molecule thallium fluoride using a rotationally cold beam from a jet source. Our method was to search for a frequency shift of the thallium nuclear magnetic resonance when an external electric field of 29.5 kV/cm was reversed with respect to a magnetic quantization axis. The measured shift, (1.42.4)×10-4 Hz, was interpreted as a null result and constitutes a tenfold improvement in sensitivity over the previous measurement. Accordingly, our measurement has reduced the upper limits on the proton and electron electric dipole moments and on other T-violating weak couplings that can be deduced from the frequency shift. © 1991 The American Physical Society.